Films from PVA and Sansevieria trifasciata Leaves Extracts as a Smartphone Protector with Radiation Reducing Property and Its LC-MS Analysis - Melinia Falestin; Akhiruddin Maddu; Luthfan Irfana; Purwantiningsih Sugita; Budi Arifin; Auliya Ilmiawati (Universitas Gadjah Mada, 2023)
Sansevieria trifasciata (mother-in-law's tongue), an ornamental plant widely found in Indonesia, can absorb electromagnetic radiation in various electronic devices. This study aims to find the best S. trifasciata extract as an electromagnetic and thermal radiation reducer emitted from a smartphone. S. trifasciata leaves were macerated using ethanol, acetone, and dichloromethane. The extract was mixed with PVA as a film and tested for electromagnetic radiation using a radiation measuring device type GM-3120. Thermal radiation was tested using a temperature sensor (PASCO CI-6505B) connected to a PASCO 550 Universal Interface. All smartphone protective films decreased radiation from the smartphone, and the acetone extract caused the most significant radiation decrease, with the best results at a concentration of 5%. An S. trifasciata extract contained alkaloids, saponins, steroids, phenolics, and tannins based on the phytochemical tests. Based on LC-MS data, the dominant compounds identified from the three extracts of S. trifasciata is a group of alkaloids, fatty acid, and steroid. The functional groups that are thought to play a role in reducing radiation are the C-O, C=O, and C-OH functional groups. A compound that is thought to contribute to the reduction in radiation is neuroscogenin, a steroid group.